Implementasi Sistem Informasi Absensi dan Nilai Berbasis Web di SMA Islam Al-Kahfi Somalangu Kebumen dengan Metode Waterfall - kurniawan, Agung; Fadjeri, Akhmad; Hidayat, Taufik (Jurnal Kridatama Sains dan Teknologi, 2024)
In the continuously evolving digital era, the application of information technology in education has become crucial, especially for managing data efficiently and accurately. This study aims to develop a web-based attendance and grading information system at SMA Islam Al-Kahfi Somalangu Kebumen using the Waterfall method. SMA Islam Al-Kahfi, as a proactive educational institution, requires a system capable of integrating real-time student attendance management and grade evaluation to improve the quality of the teaching and learning process. This system development follows five main stages of the Waterfall method: (1) Requirements Analysis, where user needs are gathered and analyzed to determine system specifications; (2) System Design, which includes database design, user interface, and system architecture; (3) Implementation, involving the coding process and integration of system components; (4) Testing, using black-box methods to ensure all system functions work as intended without examining internal structures; and (5) Maintenance, to ensure the system continues to function well and can be updated as needed. The research results show that the developed information system successfully meets SMA Islam Al-Kahfi's needs for managing student attendance and grades. This system not only enhances efficiency in recording attendance and processing grades but also facilitates data access for teachers and administrative staff through an intuitive and user-friendly interface. End-user testing indicates that the system functions well, meets expectations, and is ready for full implementation. It is hoped that this system will make a significant contribution to improving the quality of school administrative services, particularly in attendance and grading management. The application of the Waterfall method in system development has proven effective in producing a structured, stable system that meets user needs